(untitled) (Polish Yearbook of International Law, 2021)
This article examines the idea of cross-currents in international law, which was proposed almost a century ago by Ludwik Ehrlich. First the theoretical background of this idea is provided, with the focus on Albert Venn Dicey’s assumption that there are fundamental differences in public opinion influencing the legislative process. The development of the crosscurrents concept is given through the prism of the evolution of Ehrlich’s ideas. The article illustrates some aspects of his legal philosophy, which describe the scholar as broad-minded, innovative, and deep-thinking. Four dimensions of cross-currents in international law are discussed: (1) the existence of norms originating from different periods; (2) variations between states in their recognition and interpretation of them; (3) fulfillment of abstract norms; and (4) inconsistencies of theory and practice. They contribute to approximating a fully coherent international law serving as the ideal in comparison to a heterogeneous, contradictory, fragmented one, as is frequently observed at the present time. The idea of cross-currents might be helpful in accepting the view that some of the incompatibilities between the rules and principles of international law are inevitable and do not cause harm to international legality.